Nursing during the COVID‐19 pandemic: A reflective thematic analysis of how the hamster wheel shifted personal and professional control. Issue 5 (19th January 2023) - Nelson, Heather; Hubbard Murdoch, Natasha; Ziefflie, Beverlee; Norman, Kasandra; Black, Milly H. C.; Rudolph, Sherri
Abstract: Aim: The aim of this national study was to examine the experience of nurses 9–12 months after the onset of the pandemic. Design: This article reports the reflective thematic analysis of the qualitative portion of a mixed methods study of the experiences of 1319 Canadian nurses between February to May 2021. Methods: Data gathering occurred through open‐text box questions in an online survey. Results: Three overarching themes were found: (1) the hamster wheel, (2) the shifting sense of control, and (3) the inability to leave the pandemic at work. Conclusion: This research presents a national perspective of nurses which contributes to the wider global narrative. The experience of redeployment, nurses as decision‐makers, communication and leadership challenges were all factors impacting mental health and intraprofessional collaboration. Implications for the Profession: The findings revealed the immense pressure, mental health concerns, and professional implications for nurses in all domains. Public or Patient Contributions: No public or patient contributions.